2007
DOI: 10.1007/s00213-007-0977-7
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine effects on affective response in depression-prone smokers

Abstract: Self-administering nicotine appears to improve depression-prone smokers' emotional response to a pleasant stimulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 74 publications
3
55
2
1
Order By: Relevance
“…Segundo Ismail, Sloggett e Stavola (2000), indivíduos deprimidos têm baixa autoestima, são pessimistas e tornam-se negligentes relativamente à sua saúde, adotando comportamentos de risco, como fumar. Segundo Spring et al (2008), em fumadores deprimidos, o comportamento tabágico agrava o afeto negativo. Outros fumadores relatam que usam o tabaco como meio para reduzir a ansiedade para atenuar as anomalias afetivas e neurobiológicas associadas ao seu problema psicológico (Feldner et al, 2009).…”
Section: Discussionunclassified
“…Segundo Ismail, Sloggett e Stavola (2000), indivíduos deprimidos têm baixa autoestima, são pessimistas e tornam-se negligentes relativamente à sua saúde, adotando comportamentos de risco, como fumar. Segundo Spring et al (2008), em fumadores deprimidos, o comportamento tabágico agrava o afeto negativo. Outros fumadores relatam que usam o tabaco como meio para reduzir a ansiedade para atenuar as anomalias afetivas e neurobiológicas associadas ao seu problema psicológico (Feldner et al, 2009).…”
Section: Discussionunclassified
“…45 In a second study, among smokers with current or past depression, RNC cigarettes were less effective than NNC cigarettes at increasing positive mood and reducing negative mood during positive mood induction, but NNC cigarettes also exacerbated the effects of negative mood induction on negative mood. 46 Another study found that smokers with a history of depression smoked more NNC and RNC cigarette puffs during either neutral or negative mood induction, suggesting that they experience stronger acute reinforcing effects of smoking in general, regardless of nicotine content or mood. 47 To our knowledge, the current study is the first to examine the effects of an extended period of RNC cigarette use among people with elevated depressive symptoms, and the first to assess multiple behavioral, subjective, and physiological measures relevant to estimating the potential effects of a nicotine reduction policy in these smokers.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between changes in positive affect and risk for smoking lapse has received far less attention than negative affective processes. Although mechanisms for the functional role of nicotine and a nicotine withdrawal -related shift in the experience of rewards have been hypothesized ( Cook et al, 2004 ;Spring et al, 2008 ), further research is needed to understand factors that may infl uence changes in positive affect clinically. Changes in positive affect prior to attempts at cessation may present a new target for improving treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in negative affect ( Brown et al, 2001 ;Hall et al, 1996 ;Spring et al, 2008 ) and decreases in positive affect ( al ' Absi et al, 2004 ;Spring et al, 2008 ) during cessation have been proposed as mechanisms for relapse that may be concentrated among depression-prone smokers. For example, depression-prone smokers are more likely to report smoking when experiencing negative affect ( Brandon, 1994 ) and have demonstrated an enhanced response to positive affect situations when selfadministering nicotine ( Spring et al, 2008 ).…”
Section: Original Investigationmentioning
confidence: 99%
See 1 more Smart Citation